Laboratory Safety Knowledge, Attitudes, Practices, and Compliance among Secondary School Pre-service Science Teachers: A Pilot Study - Wan Ahmad Yanee, Wan Solihin; Hamidi, Noor Najihah; Firus Khan, Al 'Aina Yuhainis; Jianlei, Cao; Said, Hardimah Md; Syed Aris, Sharipah Ruzaina (Jurnal Pendidikan IPA Indonesia, 2025)
Effective laboratory safety is central to quality science education, yet limited evidence exists on Malaysian teachers' preparedness and adherence to safety standards. This pilot study aimed to validate an instrument measuring knowledge, attitudes, and practices (KAP) toward laboratory safety and to explore preliminary findings among pre-service secondary school science teachers. A cross-sectional pilot study was conducted with 30 pre-service teachers from Universiti Teknologi MARA (UiTM). Data was collected using a self-developed KAP questionnaire and a safety facilities checklist, both reviewed by experts for content validity. Item analysis was used for knowledge questions, while internal consistency was assessed using Cronbach's alpha for attitude and practice domains. Descriptive statistics summarised KAP levels and the availability and functionality of safety facilities. Knowledge items showed acceptable difficulty (p = 0.50–0.80) and discrimination (D = 0.30–0.80). Reliability was strong, with Cronbach's alpha values of 0.901 (attitude) and 0.905 (practice). Most respondents demonstrated high knowledge (70%) and universally positive attitudes (100%), yet practices were less consistent, with 23.3% reporting only moderate adherence. Laboratory facilities were largely available (87.5%), but functionality was low (32.7%), with deficiencies in safety data sheets (36.7%), chemical expiry records (40.0%), and first aid kits (56.7%). This pilot study highlights a disparity between pre-service teachers’ knowledge and their actual laboratory practices, further constrained by poorly maintained safety facilities. The reporting of validity and reliability findings demonstrates that the instrument is robust and suitable for larger-scale investigations. Strengthening laboratory safety in schools requires targeted professional development, systematic facility maintenance, and consistent monitoring mechanisms.